Experiment on the Effectiveness of Audio-Visual TV Media as a Tool for Language Development in Early Childhood - Rici Oktari; Aan Kudrotulloh; Prety Citra Pratesi; Meysi Apriliani; Febri Yuridnir Rahimah (STAI Publisistik Thawalib Jakarta, 2025)
Language development in early childhood is influenced by interactions with parents, teachers, and the surrounding environment. The use of audio-visual media, such as animated films, has the potential to enhance young children’s language abilities in early childhood education settings. This study aims to evaluate the effect of audio-visual media on the development of early childhood language skills through interaction with animated films. The research employed a One-Group Pretest-Posttest experimental design with direct observation and inferential statistical analysis (validity and normality tests, and a t-test). Based on the t-test results, the pretest had a significant effect on the posttest (p = 0.024), which is less than 0.05. This indicates a significant difference in children’s language abilities before and after the use of audio-visual TV media at Raudhatul Athfal Al-Quraniyah, South Bengkulu. Therefore, it can be concluded that children’s engagement in watching animated films positively impacts the development of early childhood language skills, demonstrating the effectiveness of audio-visual media in supporting early language development.